Automatic Stove Control System Based on the NodeMCU ESP8266 Microcontroller - Muhammad Nauval Khoiron Hamdani; Indah Sulistiyowati; Shazana Dhiya Ayuni (Journal of Electrical Technology UMY, 2022)
A stove is a handy tool for humans. The use of stoves in everyday life brings beneficial and detrimental impacts. A stove is a tool used to help human activities, but the impact of its weakness can cause household accidents caused by the negligence of the community itself. The NodeMCU-based automatic hob was built to address this problem. This stove can set the cooking time and automatically stop working at the specified time. This stove can also turn off automatically if the sensor does not detect the presence of people around to minimize the occurrence of household accidents. This automatic stove is expected to be a technological reformer in household appliances and a solution to reduce the number of accidents caused by stoves.